Servizi satellitari COPERNICUS e GALILEO - ASI Agenzia Spaziale Italiana (Archeomatica, 2018)
ASI, the Italian Space Agency, is engaged with various national, European and international initiatives, in the transfer of technology and in the development of the downstream sector of applications based on satellite services such as Galileo and Copernicus.